Comparing communication strategies for reducing residential water consumption. (March 2015) - Seyranian, Viviane; Sinatra, Gale M.; Polikoff, Morgan S.
Abstract: The current study tested the effectiveness of four different water conservation interventions drawn from the social psychological literature. 374 households in an affluent neighborhood in Los Angeles County were randomly assigned to receive one of four possible communications that either evoked social norms, social identity, personal identity, or the knowledge deficient approach (water saving tips). Each household's actual water consumption was measured at baseline (pre-intervention), in the short-term (1 week post intervention) and the long term (4 weeks post-intervention). The results of the study indicated that for high water consumers at baseline, the knowledge deficit approach resulted in a more water consumption than the other three conditions in the short term and long term. These results imply that the social norms, social identity, or personal identity approaches provided more promising avenues to encourage water conservation than the knowledge deficit approach. Implications of these results are discussed. Highlights: Water usage was tested after households received one of four interventions. The knowledge deficit approach may not be effective for water conservation. Households receiving water saving tips used more water than other interventions.